Low‐grade inflammatory polarization of monocytes impairs wound healing. Issue 4 (25th January 2016) - Yuan, Ruoxi; Geng, Shuo; Chen, Keqiang; Diao, Na; Chu, Hong Wei; Li, Liwu
Abstract: Impaired wound healing often accompanies low‐grade inflammatory conditions, during which circulating levels of subclinical super‐low‐dose endotoxin may persist. Low‐grade inflammatory monocyte polarization may occur during chronic inflammation and deter effective wound repair. However, little is understood about the potential mechanisms of monocyte polarization by sustained insult of subclinical super‐low‐dose endotoxin. We observed that super‐low‐dose endotoxin preferentially programmes a low‐grade inflammatory monocyte state in vitro and in vivo, as represented by the elevated population of CD11b + Ly6C high monocytes and sustained expression of CCR5. Mechanistically, super‐low‐dose endotoxin caused cellular stress, altered lysosome function and increased the transcription factor IRF5. TUDCA, a potent inhibitor of cellular stress, effectively blocked monocyte polarization and improved wound healing in mice injected with super‐low‐dose endotoxin. Our data revealed the polarization of low‐grade inflammatory monocytes by sustained endotoxin challenge, its underlying mechanisms and a potential intervention strategy. Copyright © 2015 Pathological Society of Great Britain and Ireland. Published by John Wiley & Sons, Ltd.